Chinese version of exercise dependence scale-revised: psychometric analysis and exploration of risk factors - Shao, Yingbo; Zhang, Haoyu; Zhang, Xiaonan; Liang, Qian; Zhang, Hui; Zhang, Feifei (Frontiers in Psychology, 2023)
Exercise addiction (EA) is a dysfunctional behavior characterized by exaggerated training which has adverse effects on physiology and psychology. To examine the reliability and validity of the Chinese version of the Exercise Dependence Scale-Revised (EDS-R) and the social and psychological aspects related to EA, a large sample behavioral study was conducted. College students were selected as the target group. All of them were asked to finish the scales about exercise, including the Chinese version of EDS-R and the Motives for Physical Activity Measure-Revised scales. A confirmatory factor analysis, Mann-Whitney U test, and hierarchical regression test were performed to test the reliability and validity of the Chinese version of EDS-R and find the explanatory variables of EA. A total of 837 (556 female) students with a mean age of 20.38 years were recruited in the present study. The Chinese version of EDS-R showed good reliability and validity (McDonald's ω=0.973, CR=0.99, AVE=0.80) in Chinese college students. EA was positively correlated with exercise frequency and ability motivation across the study sample.Besides, the Mann-Whitney U test revealed that the exercise motivation difference is the primary cause of the gender gap in EA. The Chinese version of EDS-R is a relatively robust and accurate instrument to assess the risk of EA. Additionally, exercise frequency and motivation may be the potential risk factors for EA. The screening of risk factors is of great significance for the early detection and prevention of EA.